Perbandingan Kinerja Reksadana Saham Syariah dan Konvensional (Pada 10 Reksadana di BEI Tahun 2017-2019) - Mufidah, Evi Nailul; Agusvinatassari, Dhuwik Iffuk; Hana, Kharis Fadlullah (IAIN Surakarta, 2020)
This research was conducted with the aim to find out, describe, and to analyze how the comparative performance of Islamic stock mutual funds and conventional stock mutual funds, especially mutual funds registered in the same investment manager. The sample used in this study is 10 mutual funds that are members of 5 investment manager that are the same as each investment manager is one conventional stock mutual fund and one Islamic stock mutual funds listed on the IDX during the observation period in April 2017- December 2019. The results of data analysis show that the use of the sharpe method the performance of Islamic stock mutual funds is superior to that of conventional stock mutual funds. Whereas when using the Treynor index and Jensen index the results obtained if the performance of conventional stock mutual funds is higher than the performance of Islamic stock mutual funds with a fairly large difference in value. Keywords: Comparison, Performance, Mutual Funds, Conventional Stock Mutual Funds, Islamic Stock Mutual Funds.